Refined nomogram incorporating standing cough test improves prediction of male transobturator sling success. Issue 8 (1st May 2018) - Shakir, Nabeel A.; Fuchs, Joceline S.; McKibben, Maxim J.; Viers, Boyd R.; Pagliara, Travis J.; Scott, Jeremy M.; Morey, Allen F.
Abstract : Aims: To develop a decision aid in predicting sling success, incorporating the Male Stress Incontinence Grading Scale (MSIGS) into existing treatment algorithms. Methods: We reviewed men undergoing first‐time transobturator sling for stress urinary incontinence (SUI) from 2007 to 2016 at our institution. Patient demographics, reported pads per day (PPD), and Standing Cough Test (SCT) results graded 0‐4, according to MSIGS, were assessed. Treatment failure was defined as subsequent need for >1 PPD or further procedures. Parameters associated with failure were included in multivariable logistic models, compared by area under the receiver‐operating characteristic curves. A nomogram was generated from the model with greatest AUC and internally validated. Results: Overall 203 men (median age 67 years, IQR 63‐72) were evaluated with median follow‐up of 45 months (IQR 11‐75 months). A total of 185 men (91%) were status‐post radical prostatectomy and 29 (14%) had pelvic radiation history. Median PPD and SCT grade were both two. Eighty men (39%) failed treatment (use of ≥1 PPD or subsequent anti‐incontinence procedures) at a median of 9 months. History of radiation ( P  = 0.03), increasing MSIGS ( P  < 0.0001) and increasing preoperative PPD ( P  < 0.0001) were associated with failure on univariate analysis. In a multivariable model with AUC 0.81, MSIGS, and PPD remained associated ( P  = 0.002 and <0.0001 respectively, and radiation history P  = 0.06), and was superior to models incorporating PPD and radiation alone (AUC 0.77, P  = 0.02), PPD alone (AUC 0.76, P  = 0.02), and a cutpoint of >2 PPD alone (AUC 0.71, P  = 0.0001). Conclusions: MSIGS adds prognostic value to PPD in assessing success of transobturator sling for treatment of SUI.